Changing Etiologies and Prognostic Factors in Pediatric Acute Liver Failure. Issue 2 (20th December 2019) - Mendizabal, Manuel; Dip, Marcelo; Demirdjian, Ezequiel; Lauferman, Leandro; Lopez, Susana; Minetto, Julia; Costaguta, Alejandro; Rumbo, Carolina; Malla, Ivone; Sanchez, María Camila; Halac, Esteban; Cervio, Guillermo; et al.
Abstract : After the implementation of universal hepatitis A virus vaccination in Argentina, the outcome of pediatric acute liver failure (PALF) remains unknown. We aimed to identify variables associated with the risk of liver transplantation (LT) or death and to determine the causes and short‐term outcomes of PALF in Argentina. We retrospectively included 135 patients with PALF listed for LT between 2007 and 2016. Patients with autoimmune hepatitis (AIH), Wilson's disease (WD), or inborn errors of metabolism (IEM) were classified as PALF–chronic liver disease (CLD), and others were classified as "pure" PALF. A logistic regression model was developed to identify factors independently associated with death or need of LT and risk stratification. The most common etiologies were indeterminate (52%), AIH (23%), WD (6%), and IEM (6%). Overall, transplant‐free survival was 35%, whereas 50% of the patients underwent LT and 15% died on the waiting list. The 3‐month risk of LT or death was significantly higher among patients with pure PALF compared with PALF‐CLD (76.5% versus 42.5%; relative risk, 1.8 [1.3‐2.5]; P  < 0.001), and 3 risk factors were independently associated with worse outcome: international normalized ratio (INR) ≥3.5 (odds ratio [OR], 3.1; 95% confidence interval [CI], 1.3‐7.2]), bilirubin ≥17 mg/dL (OR, 4.4; 95% CI, 1.9‐10.3]), and pure PALF (OR, 3.8; 95% CI, 1.6‐8.9). Patients were identified by the number of risk factors: Patients with 0, 1, or ≥2 risk factors presented a 3‐month risk of worse outcome of 17.6%, 36.6%, and 82%, respectively. In conclusion, although lacking external validation, this simple risk‐staging model might help stratify patients with different transplant‐free survival rates and may contribute to establishing the optimal timing for LT.